Precursor effects on methylamine gas-induced CH3NH3PbI3 films for stable carbon-based perovskite solar cells. (1st November 2018) - Wei, Ya; Li, Weiping; Xiang, Sisi; Liu, Jiaming; Liu, Huicong; Zhu, Liqun; Chen, Haining
Highlights: The effects of precursor compositions on CH3 NH3 PbI3 films were investigated. The conversion mechanisms of different precursors in methylamine gas were studied. Anti-solvent treatment could help to effectively enhance interface contact. The C-PSCs achieved the highest PCE of 11.6% and exhibited high stability. Abstract: Carbon-based perovskite solar cells (PSCs) without hole transport material have attracted much attention due to their high stability. However, their power conversion efficiency (PCE) is still low because of the lack of suitable perovskite deposition methods. In this work, a facile solid-gas reaction method was explored to prepare high quality perovskite and the effects of precursor composition (PbI2, PbI2 + HI, HPbI3 and PbI2 + NH4 I) on the CH3 NH2 (MA) gas-induced perovskite were systematically investigated. The lack of H + /I − and/or HI suppressed the conversion of PbI2 precursor to MAPbI3, while rapid and complete conversion was achieved for (PbI2 + HI), HPbI3 and (PbI2 + NH4 I) precursors. Compared with HPbI3 precursor, the presence of H2 O molecules in (PbI2 + HI) precursor lowered the perovskite crystallinity, while the release of NH3 from (PbI2 + NH4 I) precursor slower the interaction of MA molecules with MAPbI3 for achieving the highest quality MAPbI3 layer. The application of an anti-solvent treatment during precursor deposition further improved the quality of HPbI3 and (PbI2 + NH4 I)-processed perovskite layers, which as a result, significantly promoted the photovoltaic performance of C-PSCs. Both devices exhibited considerably high stability, especially for the (PbI2 + NH4 I)-processed C-PSCs, who did not show any PCE degradation after storage in air atmosphere at room temperature for 120 days.